Cell fate analysis of embryonic ventral mesencephalic grafts in the 6-OHDA model of Parkinson's disease. - Sonya Carvalho Neto; Ahmad Salti; Zoe Puschban; Nadia Stefanova; Roxana Nat; Georg Dechant; Gregor K Wenning (PLoS ONE)
Evidence from carefully conducted open label clinical trials suggested that therapeutic benefit can be achieved by grafting fetal dopaminergic (DAergic) neurons derived from ventral mesencephalon (VM) into the denervated striatum of Parkinson's disease (PD) patients. However, two double-blind trials generated negative results reporting deleterious side effects such as prominent dyskinesias. Heterogeneous composition of VM grafts is likely to account for suboptimal clinical efficacy.We consider that gene expression patterns of the VM tissue needs to be better understood by comparing the genetic signature of the surviving and functioning grafts with the cell suspensions used for transplantation. In addition, it is crucial to assess whether the grafted cells exhibit the DAergic phenotype of adult substantia nigra pars compacta (SNpc). To investigate this further, we used a GFP reporter mouse as source of VM tissue that enabled the detection and dissection of the grafts 6 weeks post implantation. A comparative gene expression analysis of the VM cell suspension and grafts revealed that VM grafts continue to differentiate post-implantation. In addition, implanted grafts showed a mature SNpc-like molecular DAergic phenotype with similar expression levels of TH, Vmat2 and Dat. However, by comparing gene expression of the adult SNpc with dissected grafts we detected a higher expression of progenitor markers in the grafts. Finally, when compared to the VM cell suspension, post-grafting there was a higher expression of markers inherent to glia and other neuronal populations.In summary, our data highlight the dynamic development of distinctive DAergic and non-DAergic gene expression markers associated with the maturation of VM grafts in vivo. The molecular signature of VM grafts and its functional relevance should be further explored in future studies aimed at the optimization of DAergic cell therapy approaches in PD.